2003
DOI: 10.1310/mm9w-bau0-bt6q-401b
|View full text |Cite
|
Sign up to set email alerts
|

Compact Quadruple Therapy with the Lamivudine/Zidovudine Combination Tablet Plus Abacavir and Efavirenz, Followed by the Lamivudine/Zidovudine/Abacavir Triple Nucleoside Tablet Plus Efavirenz in Treatment-Naïve HIV-Infected Adults

Abstract: COM/ABC/EFV or TZV/EFV produced potent, durable virologic suppression and immunologic benefits, was associated with high adherence rates, and was generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Innovations in containers, labeling, and packaging include blister packs, PillPack, and a variety of adherence devices ranging from digital pill containers to dispensing devices. [13][14][15][16] Studies have shown limitations to many of these innovations, and, overall, no significant impact on adherence has resulted from the use of simple adherence devices. 17,18 Over 700 digital apps exist as reminders to improve medication adherence, but users often report technical difficulties like schedule inflexibility, since many do not take, or need to take, their medication at an exact time, as well as notification fatigue from daily timed reminders to take their medication.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…Innovations in containers, labeling, and packaging include blister packs, PillPack, and a variety of adherence devices ranging from digital pill containers to dispensing devices. [13][14][15][16] Studies have shown limitations to many of these innovations, and, overall, no significant impact on adherence has resulted from the use of simple adherence devices. 17,18 Over 700 digital apps exist as reminders to improve medication adherence, but users often report technical difficulties like schedule inflexibility, since many do not take, or need to take, their medication at an exact time, as well as notification fatigue from daily timed reminders to take their medication.…”
Section: Original Manuscriptmentioning
confidence: 99%